Problematika Kesaksian Rukyatul Hilal Orang Non Muslim - Ridhayanti, Nurul Resky (Universitas Islam Negeri Mataram, 2022)
The determination of the beginning of the month of Kamariyah is an interesting study of astronomy to be studied more deeply. In determining the beginning of the month of Kamariyah, there are two methods, namely reckoning and rukyat. The rukyat or rukyatul hilal method is related to the results of rukyat and the testimony of the new moon itself. The moment that Thierry Legault arrived, who had photographed the new moon, became a question of how his testimony was as a witness in seeing the new moon. According to the views of some schools and Islamic law, the testimony of the hilal of non-Muslims cannot be accepted because they are not just people and have no power over Muslims. But if you look at some of the conditions in the hilal testimony, Thierry Legault himself fulfills several formal and material requirements.